Foley catheter balloon tamponade for penetrating neck injuries at Groote Schuur hospital: an update - Scriba, Matthias Frank (Division of General Surgery, 2020)
Introduction Foley catheter balloon tamponade (FCBT) for bleeding penetrating neck injuries (PNIs) is an effective, readily available and easy-to-use technique. This study aims to audit the technique and highlight current investigative and management strategies. Methods All adult patients (18 years and older) with PNIs requiring FCBT presenting to Groote Schuur Hospital (GSH) within a 22-month study period were included. Data was captured from an approved electronic registry and analysed. Analysed parameters included demographics, major injuries, imaging, management and outcomes. Results Over the study period a total of 628 patients with PNI were managed at GSH, in which 95 patients (15.2%) FCBT was utilised. The majority were men (98%) with an average age was 27.9 years. Most injuries were caused by stab wounds (90.5%). The majority of catheters (81.1%) were inserted prior to arrival at GSH (1.1% prehospital, 45.3% at clinic level and 34.7% at district hospital level). Computerised tomography (CT) angiography was used in 92.6% of patients, while 8 patients (8.4%) required formal angiography. Of these, 2 were purely diagnostic and 6 were performed for definitive endovascular management. A total of 34 arterial injuries (19 major and 15 minor) were identified in 29 patients. Ongoing bleeding was noted in three patients, equating to a 97% success rate at haemorrhage control. Thirteen (13.7%) patients requried open neck surgery. Seventy-two (75.8%) patients without major arterial injury had removal of the catheter at 48-72 hours post injury. Only two of these had bleeding on catheter removal. Fifteen patients required ICU admission. A total of 36 separate morbidities were documented in 28 patients (29.5%). There were 4 deaths (4.2% mortality rate), with only one of these attributable to uncontrolled haemorrhage from the neck wound. Conclusion This large series shows the current use of FCBT for PNI. It highlights ease of use, high rates of success at haemorrhage control (97%) and good outcomes with the technique. Venous injuries and minor arterial injuries can be managed with this technique definitively.